2011
DOI: 10.1111/j.1475-097x.2011.01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Free‐living energy expenditure reduced after deep brain stimulation surgery for Parkinson’s disease

Abstract: The STN-DBS operated patients have a significant postoperative weight gain, as a result of a decrease in free-living energy expenditure concomitant with an insufficient decrease in energy intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Recently, it has been proposed to name eating abnormalities after DBS "hypo-dopaminergic snacking" rather than Binge Eating, thus emphasizing the role of dopaminergic reduction in the occurrence of these abnormalities (Kistner et al, 2014). As a final remark, the majority of the studies do not report an increase in food intake among PD patients with DBS or an improvement in appetite or change in eating habits (Bannier et al, 2009;Macia et al, 2004;Montaurier et al, 2007;Perlemoine et al, 2005;Rieu et al, 2011;Sauleau et al, 2009) but few studies report such findings (Jorgensen, Werdelin, Lokkegaard, Westerterp, & Simonsen, 2012;Nirenberg & Waters, 2006). However, as we have already argued in this review, the evaluation of food intake, via self-reported measures, may be imprecise and inaccurate.…”
Section: Weight Food Intake and Deep Brain Stimulationmentioning
confidence: 89%
“…Recently, it has been proposed to name eating abnormalities after DBS "hypo-dopaminergic snacking" rather than Binge Eating, thus emphasizing the role of dopaminergic reduction in the occurrence of these abnormalities (Kistner et al, 2014). As a final remark, the majority of the studies do not report an increase in food intake among PD patients with DBS or an improvement in appetite or change in eating habits (Bannier et al, 2009;Macia et al, 2004;Montaurier et al, 2007;Perlemoine et al, 2005;Rieu et al, 2011;Sauleau et al, 2009) but few studies report such findings (Jorgensen, Werdelin, Lokkegaard, Westerterp, & Simonsen, 2012;Nirenberg & Waters, 2006). However, as we have already argued in this review, the evaluation of food intake, via self-reported measures, may be imprecise and inaccurate.…”
Section: Weight Food Intake and Deep Brain Stimulationmentioning
confidence: 89%
“…The drop in EE following DBS was not found to be predictive of post-operative weight gain.There was no correlation between weight gain and reduction of Parkinson’s disease medications or with improvement in UPDRS IV score (measures severity of dyskinesias and motor fluctuations). While it has been proposed that an improvement in motor symptoms corrects EE[28] allows for weight gain[15], this has not necessarily been shown in the Montaurier study or other studies assessing a correlation between motoric improvement and weight change[9,10]. This led the authors to conclude that post-DBS weight gain may be due to improvement in spontaneous motor fluctuations, but that they could not rule out the possibility of an effect on central regulation of energy expenditure, possibly through stimulation of the nearby thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…After STN-DBS, a significant decrease (7–13%) of daily EE was reported (86, 145). A decrease of EE of 13% without adaptation of intake would lead to a weight gain of 20 kg after 1 year (145).…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…A decrease of EE of 13% without adaptation of intake would lead to a weight gain of 20 kg after 1 year (145). This decrease of EE after successful STN-DBS may be explained by:

a reduced resting EE (87) following improvement of rigidity and tremor,

a reduction of levodopa-induced dyskinesia (146),

reduction of OFF-period dystonia (147),

a reduction of levodopa-induced behavioral hyperactivity (121),

an improvement of sleep pattern and nocturnal hyperactivity (121, 148).

…”
Section: Parkinson’s Diseasementioning
confidence: 99%